Safety of Cardiac Catheterization at a Center Specializing in the Care of Patients with Pulmonary Arterial Hypertension. (1st December 2013) - Zuckerman, Warren A.; Turner, Mariel E.; Kerstein, Jason; Torres, Alejandro; Vincent, Julie A.; Krishnan, Usha; Kerstein, Diane; Rosenzweig, Erika B.
Abstract : Cardiac catheterization is important for the management of patients with pulmonary arterial hypertension (PAH). It is used for diagnosis, assessment, and monitoring of PAH patients, as well as to perform interventions such as balloon atrial septostomy and coil embolization of collateral vessels. Although reports on the risks of catheterization in PAH patients are scarce, many centers hesitate to perform these procedures in such fragile patients. We performed a retrospective chart review of all cardiac catheterizations performed in PAH patients over 10 years at our pulmonary hypertension center. Demographic, hemodynamic, and outcome data were collected. Complication rates were determined, and multivariate proportional hazards modeling was performed to identify predictors of catheterization‐related complications. There were 1, 637 catheterizations performed in 607 patients over 10 years. Pediatric patients accounted for 50% of these cases, 48% were performed in patients with idiopathic PAH, and 49% were performed under general anesthesia. While the overall complication rate was 5.7%, the rate of major complications was only 1.2% ( n = 20). Although there were 8 deaths during the admission following catheterization, only 4 of these were related to the procedure, yielding a catheterization‐related mortality of 0.2%. In conclusion, when performed at a pulmonary hypertension center with expertise in the care of PAH patients, cardiac catheterization is associated with low complication rates and mortality, and it should remain an important tool in the management of these patients.